Quantum Mechanics, High Energy Physics and Accelerators: Selected Papers of John S. Bell (World Scientific Series in 20th Century Physics) - Bell M. (World Scientific Pub Co Inc, 1995)
The scientific career of John Steward Bell was distinguished by its breadth and its quality. He made several very important contributions to scientific fields as diverse as nuclear physics, accelerator physics, high energy physics and the philosophy of quantum mechanics and relativity. This book contains a large part of J.S. Bell's publications, including those that are recognized as his most important achievements, as well as others that are less well known. The selection was made by Mary Bell, Martinus Veltman and Kurt Gottfried, all of whom were involved with John Bell both personally and professionally throughout a large part of his life. An introductory chapter has been written to help place the selected papers in a historical context and to review their significance.